Hubungan Pengetahuan dan Sikap Terhadap Keputusan Penggunaan Produk Skincare Pemutih Wajah Yang Mengandung Merkuri Pada Mahasiswa Universitas Singaperbangsa Karawang - Asyifa Yan Balqis; Mally Ghinan Sholih; Salman Salman (Jurnal Ilmiah Wahana Pendidikan, 2022)
Some people try to increase their self-confidence by having white skin, so they want to use facial whitening. Negative impacts can arise from the use of products that do not meet safety requirements, for example skin care that contains harmful ingredients such as mercury. The rise of facial whitening that appears on the market, triggers the desire of students to have white skin and tend to use face whiteners which mostly contain mercury. This behavior can be risky in the decision to use facial whitening product without considering the side effects. The purpose of this study was to determine the relationship between knowledge and attitudes of students at Singaperbangsa Karawang University towards the decision to use mercury-containing facial whitening. The sample in this study was 340 people and will be divided based on the faculty using the proportional random sampling method. Data was collected using a closing questionnaire. Data processing is carried out using the chi square test. From the results of the research, it is known that the students of Singaperbangsa Karawang University have 194 respondents (57.1%) who have low knowledge, 187 respondents (55%) who have negative attitudes and 176 respondents (51.8%) have negative usage decisions. The results of the analysis with the chi square test obtained a p-value of 0.008 for knowledge and 0.000 for attitudes. In accordance with the provisions of the p-value <0.05, then Ho is rejected. Can be concluded is that there is a relationship between respondents' knowledge of the decision to use mercury facial whitening product, and there is a relationship between respondents' attitudes towards the decision to use mercury-containing facial whitening product. The conclusion of this study is that knowledge has a relationship with the decision to use facial whitening products containing mercury. The attitude of the respondents has a relationship with the decision to use facial whitening products containing mercury